Generalized seizures presurgically in a cohort of children with hemispherectomy: Predictors and a potential link to surgical outcome?. (May 2018) - Liu, Ming; Ji, Taoyun; Liu, Qingzhu; Wang, Shuang; Wu, Ye; Wang, Wen; Cheng, Weike; Wang, Ruofan; Yu, Guojing; Liu, Xiaoyan; Cai, Lixin; Jiang, Yuwu
Highlights: Generalized seizures were not an absolute contraindication for hemispherectomy. Children with ESES were more likely to experience generalized seizures presurgically. Generalized seizures could not strongly predict the unfavourable surgical outcome of hemispherectomy. Focal to bilateral tonic-clonic seizure and myoclonic-atonic seizure related to unfavourable seizure outcome. Abstract: Purpose: Generalized seizures were often thought to be contraindications for hemispherectomy. However, few studies had investigated this issue comprehensively, as well as the predictors for generalized seizures in hemispheric lesion. We studied the predictors of generalized seizures and their potential link to seizure outcomes in a cohort of children who underwent hemispherectomy. Methods: A cohort of 76 children with hemispherectomy were reviewed and dichotomized into two groups with and without generalized seizures confirmed by vEEG presurgically. All preoperative evaluation data correlated to generalized seizures and postoperative prognosis were collected and analysed. Results: Of 76 patients, 11 (14.5%) cases were documented with various generalized seizures, including atypical absence (54.5%, 6/11), myoclonic (45.5%, 5/11), atonic (36.4%, 4/11), myoclonic-atonic (18.2%, 2/11), myoclonic-absence (9.1%, 1/11) and spasms (9.1%). Electrical status epilepticus during sleep (ESES) was recorded in 3 patients (27.3%, 3/11). At last follow-up, 72.7% (8/11) patients remained seizure-free. ESES was a predictor of generalized seizures (χ 2 = 4.69, P = 0.043). No correlation was found between generalized seizures and unfavourable postoperative seizure outcome ( P = 0.153). For different seizure types, focal to bilateral tonic-clonic seizures ( P = 0.020) and myoclonic-atonic seizures ( P = 0.002) might correlate with unfavourable outcomes. Conclusion: Generalized seizures were not an absolute contraindication for hemispherectomy. Those patients with ESES might experience generalized seizures presurgically. Focal to bilateral tonic-clonic seizures and myoclonic-atonic seizures pre-surgery may indicate unfavourable post-operative seizure outcomes.